2013
DOI: 10.1021/jp4078135
|View full text |Cite
|
Sign up to set email alerts
|

Energy of Step Defects on the TiO2 Rutile (110) Surface: An ab initio DFT Methodology

Abstract: We present a novel methodology for dealing with quantum size effects (QSE) when calculating the energy per unit length and step-step interaction energy of atomic step defects on crystalline solid surfaces using atomistic slab models. We apply it to the TiO 2 rutile (110) surface using density functional theory (DFT) for which it is well known that surface energies converge in a slow and oscillatory manner with increasing slab size. This makes it difficult to reliably calculate step energies because they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…1 (b). In such a z-scan the sample is displaced vertically (z-scale in Fig have been reported to migrate from terraces to steps, leading to O br vac´s-depleted terrace fringes in the proximity of [1][2][3][4][5][6][7][8][9][10][11]-oriented steps 13 . Such O br vac´s migration effect supports our results displayed in Fig.…”
Section: Steps That Feature Triangularly-shaped S T Protrusions (One mentioning
confidence: 99%
See 3 more Smart Citations
“…1 (b). In such a z-scan the sample is displaced vertically (z-scale in Fig have been reported to migrate from terraces to steps, leading to O br vac´s-depleted terrace fringes in the proximity of [1][2][3][4][5][6][7][8][9][10][11]-oriented steps 13 . Such O br vac´s migration effect supports our results displayed in Fig.…”
Section: Steps That Feature Triangularly-shaped S T Protrusions (One mentioning
confidence: 99%
“…Only a few studies [11][12][13][14][15] on vicinal rutile planes exist, but they reveal the potential of stepped surfaces to further tailor the physical and chemical properties of r-TiO 2 . Martinez et al 13 have reported the existence of oxygen vacancies at [1][2][3][4][5][6][7][8][9][10][11] step edges (O s vac´s), as these are easier to form than O br vac´s at terraces.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,19 The ⟨110⟩ step has the highest step energy even after it reconstructs, 7 and the ⟨001⟩ step has only two stable structures that are ⟨001⟩ O and ⟨001⟩ Ti steps. 19 Recently, Hardcastle et al 6 and Stausholm-Møller et al 7 computed the isolated step energies and the step−step interactions of the ⟨001⟩ step, and they showed that the ⟨001⟩ O and ⟨001⟩ Ti steps have similar step energies, and the step−step interactions for both steps are negligible. Complicating all of these step energy calculations is "odd−even" oscillations in the TiO 2 (110) surface energy with the number of layers, 23 which must be addressed carefully.…”
Section: ■ Introductionmentioning
confidence: 99%